Training Load, Immune Status, and Clinical Outcomes in Young Athletes: A Controlled, Prospective, Longitudinal Study - Blume, Katharina; Körber, Nina; Hoffmann, Dieter; Wolfarth, Bernd (Frontiers in Physiology, 2018)
Introduction: Competitive sport can be linked with an increased risk of illness. Because of additional physical and psychological strains, young athletes need an increased attention. Training can alter the immune system. Previous studies identified Epstein Barr Virus (EBV) as indicator for the immune status. The aim was to determine the interaction between training load, stress sense, immunological parameters, and clinical symptoms. Methods: A controlled, prospective, longitudinal study on young athletes (n = 274, age: 13.8 ± 1.5 yrs) with 285 controls (age: 14.5 ± 1.9 yrs) was conducted. Athletes were examined 3 times each year to determine the effects of stress factors (training hours per week [Th/w]) on selected outcome parameters (clinical [e.g. WURSS-21: 21-item Wisconsin Upper Respiratory Symptom Survey], immunological end points). Also EBV serostatus and EBV-specific IgG tiers were studied as potential immune markers. Results: Athletes (A) trained 14.9 ± 5.6 h weekly. Controls (C) showed no lower stress levels compared to A (p = 0.387). 12 % of A reported recurrent infections (C: 8.5 %, p = 0.153), the presence of an upper respiratory tract infection (URTI) was achieved in 30.7 %. EBV seroprevalence of A was 60.3 % (C: 56.6 %, p = 0.339). Mean EBV-specific IgG titer of A was 166 ± 115 U/ml (C: 137 ± 112 U/ml, p = 0.030). With increasing Th/w, higher stress levels were observed (p < 0.001). Analyzes of WURSS-21 data revealed no relationship to Th/w (p = 0.323). Also, Th/w had no relation to EBV serostatus (p = 0.057) or the level of IgG titers (p = 0.364). Discussion: Young elite athletes showed no increased sense of stress, no more recurrent infections, and no different EBV-specific serological parameters compared to controls. Also, no direct relationship between training loads, clinical complaints, and EBV-specific immune responses was found. With increasing training loads athletes felt more stressed, but significant associations to EBV-specific serological parameters were absent. In summary, EBV serostatus and EBV-specific IgG titers do not allow risk stratification for impaired health. Further investigations are needed to identify additional risk factors and immune markers, with the aim to avoid inappropriate strains.